Perceived meaning of life and satisfaction with life: A research synthesis using an online finding archive - Sameer, Yomna; Eid, Yasmine; Veenhoven, Ruut (Frontiers in Psychology, 2023)
Meaning and happiness are main topics in Positive Pychology but their relation is not well understood. A first step to better understanding is to inspect the pattern of correlations. In this paper we focus on the relation between perceived meaning of life and satisfaction with life, taking stock of the available research findings on their co-occurrence. Specifically we seek answers to the following questions of fact • Is there a correlation between perceived meaning of life and satisfaction with life? • What kinds of meaning are most/least associated with happiness? • What sources of meaning are most least associated with happiness? • How strong are these correlations? • How variable across persons and situations? • Do the correlations differ across components of happiness? We use the World Database of Happiness, which holds standardized descriptions of 132 observed relations between perceived meaning of life and satisfaction with life. The technique of this online finding archive allows a condensed presentation of the rich findings while providing the reader access to full detail of the underlying studies. We find that perceived meaning of life and satisfaction of life are closely related at the micro-level of individuals, but not at the macro-level of nations. The possible causal mechanisms behind these correlations are explored.